A remarkable new Manihot (Euphorbiaceae) from the coastal sand plains of Sergipe, Brazil - Martins, Márcio Lacerda Lopes; de Carvalho, Paulo Cezar Lemos; Amorim, André Márcio (Phytotaxa, 2011)
Manihot breviloba P.Carvalho & M.Martins is described and illustrated. This species is distinguished from other Manihot species by its vine-like habit, petioles clasping and leaves with extremely reduced lateral lobes.